Users' satisfaction towards quality non clinical hospital facilities : an indicative preliminary survey at Teluk Intan Hospital / Anis Syafika Binti Mohd Saupi and Mohd Fadzil Bin Yassin - Mohd Saupi, Anis Syafika; Yassin, Mohd Fadzil (2019)
User's satisfaction is one of the key indicators for facilities services quality indicators that measures the level of service by facilities management provider in healthcare sector. Althought direct evaluation has already taken place literature is scarce in terms of the level of satisfaction by the user that has on perceive service quality. The aim of this study was to improve the quality of facilities and services provided for users at non-clinical hospital and to analyses the provision of the facilities provided in a non-clinical hospital. The few method instrument was used to collect the data. That user that pointed were respondents to the questionnaire. Exploratory analysis was used to test research hypotheses. This was supported by an exploratory case study of a recently completed non-clinical hospital. A patient satisfaction questionnaire was designed for data collection where it was distributed into three groups consisting of out-patients, visitors and staff at the non-clinical hospital. This is to identify the users' satisfaction on the facilities and services provided at the non-clinical hospital. This paper to recommend the best approach in improving user satisfaction on facilities and services in hospital.